Coexistence of systemic lupus erythematosus, tuberous sclerosis and aggressive natural killer-cell leukaemia: coincidence or correlated?. (June 2016) - Olde Bekkink, M; Ahmed-Ousenkova, Y M; Netea, M G; van der Velden, W J; Berden, J H
Among patients with systemic lupus erythematosus (SLE) there is an increased risk of haematological malignancies, especially non-Hodgkin lymphoma. However, the association of SLE with aggressive CD3 negative natural killer (NK)-cell leukaemia has not been reported so far. We present a case of a 39-year-old woman with SLE, aggressive NK-cell leukaemia and tuberous sclerosis complex. The prior probability of developing the combination of these three rare diseases by coincidence is extremely low (<10 −13 ). Possible underlying immunological, genetic and toxic/environmental pathways are discussed.